Quality of life benefits from arrhythmia ablation: A longitudinal study using the C‐CAP questionnaire and EQ5D. Issue 6 (17th April 2019) - Evans, James M.; Withers, Kathleen L.; Lencioni, Mauro; Carolan‐Rees, Grace; Wood, Kathryn A.; Patrick, Hannah; Griffith, Michael
Abstract: Aims: To investigate long‐term efficacy of cardiac ablation for symptomatic arrhythmia by gathering generic and arrhythmia‐related quality of life data using patient‐reported outcome measures before and after ablation. Methods: Consecutive patients undergoing cardiac ablation procedures at three sites in the United Kingdom were enrolled (n = 561). Data were collected at baseline, at 8–16 weeks, and 12 months after the ablation with responses from 390 patients received at all three time points. Nonparametric tests were used to identify any changes in patient outcomes due to nonnormal data. Results: There were significant improvements in symptom severity, impact on life scores, EQ‐5D‐5L indices, and visual analogue score (VAS) scores at pre‐ versus 3 months and at preablation versus 1 year. Impact on life score showed additional improvement at 1 year versus 3 months, while improvements in symptom severity, EQ‐5D‐5L indices, and VAS scores continued to be maintained between 3 months and 1 year. Conclusion: Cardiac ablation provides patients with arrhythmias relief from symptoms, and results in an improvement in quality of life. Improvements observed at 3 months are maintained at 1 year follow‐up. Condensed Abstract: Questions remain regarding the long‐term efficacy of cardiac ablation. We enrolled 561 consecutive patients undergoing ablation procedures at three UK sites. Data were collected at baseline, and at 3 and 12 months. Improvement in symptoms was reported following treatment, with patients continuing to maintain or show continued improvement at 1 year.